Introducing practical tools for fit to drive assessment of the elderly: A step toward improving the health of the elderly - Saiedeh Bahrampouri; Hamid Reza Khankeh; Seyed Ali Hosseini; Mohammadreza Mehmandar; Abbas Ebadi (Wolters Kluwer Medknow Publications, 2021)
Today, as age increases, the demand for independent living has increased. Since driving is one of the safest and preferred ways for the elderly to travel, paying close attention to the accurate assessment of the elderly's driving ability can prevent traffic accidents in this age group. The purpose of this study was to identify and introduce practical tools for drive assessment fitness of the elderly. This systematic review was conducted according to Cochrane methodology and reported findings according to PRISMA. The following databases were searched from PubMed, ISI web of knowledge, Scopus, ProQuest, Medlib, SID, Magiran, Iran doc, and Iran Medex based on the population intervention comparison outcome method. The total records involving 12 main tools were assessed from 26 selected records in the final evaluation. The research findings indicated the selection of seven tools in the psycho-cognitive function domain such as TMT-B, Clock Drawing Test, MAZE, Montreal Cognitive Assessment, GDS-15, MMSE, and ACE-R, three tools in the sensory function domain such as Snellen, Confrontation Visual field, and Whispered Voice Test, and also two tools in motor function domain such as Rapid pace walk, and Manual test of the range of motion. The findings led to selecting practical, accurate, and fast tools for widespread use for the assessment of driving competencies of the elderly. Therefore, it is recommended that the selected tools be used in practical batteries to assess the driving skills of the elderly.